E-Selectin-Overexpressing Mesenchymal Stem Cell Therapy Confers Improved Reperfusion, Repair, and Regeneration in a Murine Critical Limb Ischemia Model - Quiroz, Hallie J.; Valencia, Samantha F.; Shao, Hongwei; Li, Yan; Ortiz, Yulexi Y.; Parikh, Punam P.; Lassance-Soares, Roberta M.; Vazquez-Padron, Roberto I.; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2022)
Aims: Novel cell-based therapeutic angiogenic treatments for critical limb ischemia patients may afford limb salvage. Mesenchymal stem cells (MSC) do not overexpress E-Selectin, however we’ve previously demonstrated the cell-adhesion molecule’s vital role in angiogenesis and wound healing. Thus, we created a viral vector to overexpress E-selectin on MSC to increase their therapeutic profile. Methods and Results: Femoral artery ligation induced hindlimb ischemia in mice and intramuscular injections were administered of vehicle or syngeneic donor MSC, transduced ex vivo with an adeno-associated viral vector to express either GFP+ (MSCGFP) or E-selectin-GFP+ (MSCE-selectin-GFP). Laser Doppler Imaging demonstrated significantly restored reperfusion in MSCE-selectin-GFP treated mice versus controls. After 3 weeks, the ischemic limbs in mice treated with MSCE-selectin-GFP had increased footpad blood vessel density, H&E ischemic calf muscle sections revealed mitigated muscular atrophy with restored muscle fiber size, and mice were able to run further before exhaustion. PCRArray-based gene profiling analysis identified 9 upregulated pro-angiogenic/pro-repair genes and downregulated TNF gene in MSCE-selectin-GFP-treated limb tissues, indicating that the therapeutic effect is likely achieved via upregulation of pro-angiogenic cytokines and downregulation of inflammation. Conclusion: This innovative cell-therapy confers increased limb reperfusion, neovascularization, improved functional recovery, decreased muscle atrophy and thus offers a potential therapeutic method for future clinical studies.